COST-EFFECTIVENESS ANALYSIS BIAYA PENGOBATAN EPILEPSI JENIS GRAND MAL DENGAN BEBERAPA OBAT ANTI EPILEPSI DI RAWAT INAP RSUD SIDOARJO - Andri Priyoherianto; Ismu dwi supangkat (AFAMEDIS, 2021)
Epilepsy is a neurological disoder that arises suddenly and periodically, ussualy with change in consciousesness. Different use of anti-epileptic drugs by patients results in patient’s medical cost increase. The use expensive anti-epileptic drugs does not guarantee the effectiveness of patient care, therefore a research needs to be done to determine which anti-epileptic drugs therapy is more cost-effective between Valproic Acid, Na Fenitoin, and combination Na Fenitoin + Valproic Acid in hospitalized epileptic patients in RSUD Sidoarjo. The Research was a retrospective observational study with retrospective data retrieval. The research was conducted a medical Record retrieval at SIM RS from January 2020- December 2020. The samples in this study were 30 patients with 7 patients using Valproic Acid, 6 patients using Na Fenitoin, and 17 patient using combination Na Fenitoin + Valproic Acid. The results showed that the more cost- effective therapy between Valproic Acid, Na Fenitoin and combination Na Fenitoin + Valproic Acid in the treatment of epileptic in RSUD Sidoarjo was therapy with combination Na Fenitoin + Valproic Acid, which can be seen from ACER ( Average Cost-Effectiveness Ratio) combination Na Fenitoin + Valproic Acid Rp Rp. 880.854 /effectiveness compared with Valproic Acid ACER value of Rp. 977.307/effectiveness and Na Fenitoin Rp. 979.546/effectiveness. The lowest ICER value on combination Na Fenitoin + Valproic Acid was Rp.-994.290. Keywords : Cost-effectiveness analysis, Combination Na Fenitoin + Valproic Acid, Epileptic